Interlaboratory comparisons of the calibration results of signal generator - Velychko, Oleh; Shevkun, Sergii; Mescheriak, Oleh; Gordiyenko, Tetyana; Kursin, Sergii (Eastern-European Journal of Enterprise Technologies, 2019)
The data of interlaboratory comparisons of calibration results of signal generators at three calibration points are presented. The choice of methodology for processing the results of interlaboratory comparisons is made taking into account the long-term drift of the comparison sample. The modernization and research of the comparison sample for interlaboratory comparisons of calibration results of signal generators are carried out. The assigned values for the three calibration points and their extended uncertainties are determined. Expressions are obtained for the approximation of the long-term drift of the comparison sample and uncertainty budgets for all assigned values of the comparison sample at the frequencies of 130 MHz, 168 MHz and 223 MHz are compiled. The interlaboratory deviations of the results obtained by laboratories are determined and the consistency of the data obtained using the En and z indicators is estimated. This characterizes the reliability and accuracy of laboratory measurement results, and is also important for confirming technical competence. The presented results of interlaboratory comparisons of the signal generator calibration results show that all participating laboratories meet the requirements by the En indicator. At the same time, two out of ten laboratories require certain substantial corrective measures, as they do not meet the requirements by the z indicator. It is established that the En indicator is not always self-sufficient. It largely characterizes only the reliability of laboratory measurement results. For this purpose, the z indicator is more informative, which provides more information on the accuracy of laboratory measurement, that is, the proximity of measurement results to the true value.